PENGARUH ATMOSFIR TOKO DAN KESESUAIAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PUNCAK DEPARTEMENT STORE BENGKULU - Tito Irwanto; Herry Novrianda; Aji Purnomo (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Tito Irwanto, Herry Novrianda, Aji Purnomo; This study aims to determine the positive effect between atmosphere and price suitability on purchasing decisions for consumers visiting the Peak of the Bengkulu City Department Store. The number of samples is 100 visitors using the multiple linear regression method. The method of analysis used in this study is multiple linear regression. The results of this study are that there is an influence of the atmosphere on purchasing decisions on consumers visiting the Peak of the Bengkulu City Department Store, this is evident in the value of tcount>ttable of 12.839> 1.66 and there is an influence of price suitability on purchasing decisions on consumers visiting the Peak Department of Store of the City of Bengkulu, this is evident in the value of t> t table of conformity of the price of 2.267> 1.66. Based on the comparison of the value of Fcount with Ftable, it is known that the Fcount value is greater than the Ftable value that is 114.992> 3.09, then the hypothesis is accepted, meaning that there is a simultaneous influence between the atmosphere and the suitability of prices towards purchasing decisions on consumers at the Top of the Department Store Store in Bengkulu City. Keywords : Atmosphere, Price Match, and Purchase Decision